2012
DOI: 10.1111/jfd.12016
|View full text |Cite
|
Sign up to set email alerts
|

Do wild fish species contribute to the transmission of koi herpesvirus to carp in hatchery ponds?

Abstract: The koi herpesvirus (KHV) has spread worldwide since its discovery in 1998 and causes disease and mortality in koi and common carp populations with a high impact on the carp production industry. Many investigations have been conducted to examine ways of distribution and to identify possible transmission vectors. The answers, however, raise many new questions. In the present study, different wild fish species taken from carp ponds with a history of KHV infection were examined for their susceptibility to the vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…Carassius auratus) may increase the difficulty in the detection of CyHV-3 during fish transfer and contribute for the distribution of the virus. (Eide et al, 2011;El-Matbouli and Soliman, 2011;Fabian et al, 2013;Reed et al, 2014). The first outbreak of koi herpesvirus disease in East Asian and Southeast Asian can be traced back to 1998 in Korea (Lee et al, 2012), 2002 in Indonesia (Sunarto et al, 2005) and 2003 in Japan (Sano et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Carassius auratus) may increase the difficulty in the detection of CyHV-3 during fish transfer and contribute for the distribution of the virus. (Eide et al, 2011;El-Matbouli and Soliman, 2011;Fabian et al, 2013;Reed et al, 2014). The first outbreak of koi herpesvirus disease in East Asian and Southeast Asian can be traced back to 1998 in Korea (Lee et al, 2012), 2002 in Indonesia (Sunarto et al, 2005) and 2003 in Japan (Sano et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cyprinidae [23], but also in other fish families, e.g. acipenseridae [26] or percidae [26,27]. Earlier studies on KHV led [37] and [38] to conclude that KHVD cannot be transferred to fish other than C. carpio.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the disease has never been found within other fish than C. carpio, namely in common carp and koi, did not detract from the ------------1 21 st 29 -32 + -+ -----+ 2 -------28 28 -+ + 3 29 -30 + -+ 31 29 29 + + + 4 31 --+ --30 28 28 + + + 5 28 --+ ------- possibility of virus replication in other fish species and investigations were not conducted to investigate the role of KHVD transmission through vector fish species, i.e., its transfer as an infectious agent to naive carp detected by a combination of virological and serological methods other than in carp or koi [38]. It has since been found that a lot of other fish species such as goldfish, crucian carp, different sturgeon species, grass carp (Ctenopharyngodon idella), silver carp (Hypophthalmichthys molitrix) or tench (Tinca tinca) may be act as a healthy appearing carrier hosts which can transfer the KHV to naive carp or koi [22,24,26,27,39]. KHVD has never occurred in any of those fish species when inoculated with KHV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…goldfish (Carassius auratus) Bergmann et al 2010;El-Matbouli and Soliman 2011;Radosavljevic et al 2012), grass carp (Ctenopharyngodon idella) ), silver carp (Hypophthalmichthys molitrix) (Kempter et al 2012;Radosavljevic et al 2012), common bream (Abramis brama) (Kempter et al 2012), tench (Tinca tinca) (Fabian et al 2012;Kempter et al 2012;Radosavljevic et al 2012), some non-cyprinid species such as ruffe (Gymnocephalus cernua), spined loach (Cobitis taenia) (Kempter et al 2012), European perch (Perca fluviatilis) (Fabian et al 2012;Kempter et al 2012), and even Atlantic sturgeon (Acipenser oxyrinchus) ). Some fishes were even able to transmit CyHV-3 to naïve common carp, for example goldfish (Bergmann et al 2010;El-Matbouli et al 2011;Radosavljevic et al 2012), grass carp, silver carp (Kempter et al 2012;Radosavljevic et al 2012), common bream (Kempter et al 2012), tench (Fabian et al 2012;Kempter et al 2012;Radosavljevic et al 2012), ruffe (Kempter et al 2012) and European perch (Kempter et al 2012). For this reason, it is necessary to verify susceptibility to CyHV-3, as well as determining species which can act as carriers for susceptible species.…”
mentioning
confidence: 99%